High Emotional Similarity Will Enhance the Face Memory and Face-Context Associative Memory - An, Shu; Zhao, Mengyang; Qin, Feng; Zhang, Hongchi; Mao, Weibin (Frontiers in Psychology, 2022)
Previous research has explored how emotional valence (positive or negative) affected face-context associative memory, while little is known about how arousing stimuli that share the same valence but differ in emotionality are bound together and retained in memory. In this study, we manipulated the emotional similarity between the target face and the face associated with the context emotion (i.e., congruent, high similarity, and low similarity), and examined the effect of emotional similarity of negative emotion (i.e., disgust, anger, and fear) on face-context associative memory. Our results showed that the greater the emotional similarity between the faces, the better the face memory and face-context associative memory were. These findings suggest that the processing of facial expression and its associated context may benefit from taking into account the emotional similarity between the faces.